Polatuzumab Vedotin Plus Rituximab, Gemcitabine, and Oxaliplatin in Relapsed or Refractory Diffuse Large B-Cell Lymphoma: Results From the Phase III, Randomized POLARGO Trial - Matthew Matasar; Zhiming Li; Theodoros P. Vassilakopoulos; Juan-Manuel Sancho; Andreas Viardot; Andrew McMillan; Mehmet Sinan Dal; Juliana Pereira; Jin Seok Kim; Lugui Qiu; Connie Lee Batlevi; Rania Ibrahim; et al. (Journal of Clinical Oncology, 2026)
PURPOSE Patients with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) face an unfavorable prognosis once first-line treatment fails; therefore, there is an unmet need for new treatment options. We evaluated the efficacy and safety of polatuzumab vedotin plus rituximab, gemcitabine, and oxaliplatin (Pola-R-GemOx) as an alternative therapy in patients with transplant-ineligible R/R DLBCL. METHODS The phase III POLARGO trial was a randomized, open-label, global study. Following a Pola-R-GemOx safety run-in (n = 15), patients with R/R DLBCL (not otherwise specified or transformed indolent lymphoma) ineligible for autologous stem cell transplant were randomly assigned 1:1 to receive Pola-R-GemOx or R-GemOx alone every 21 days for up to eight cycles. The primary end point was overall survival (OS). RESULTS In total, 255 patients were randomly assigned to receive Pola-R-GemOx (n = 129) or R-GemOx (n = 126). After a median follow-up of 24.6 months, patients receiving Pola-R-GemOx versus R-GemOx had a significantly lower risk of death (hazard ratio, 0.6 [95% CI, 0.43 to 0.83]; P = .0017) with a median OS of 19.5 months (95% CI, 13.3 to not estimable) versus 12.5 months (95% CI, 8.9 to 15.8). The most common grade 3/4 adverse events (AEs) were thrombocytopenia and neutropenia. Peripheral neuropathy was more common with Pola-R-GemOx (n = 73 [57%]) versus R-GemOx (n = 36 [29%]) and was primarily grade 1. Fatal AEs occurred in 15 (12%) and five (4%) patients in the Pola-R-GemOx and R-GemOx groups, respectively, and were largely driven by infections (including COVID-19). CONCLUSION Pola-R-GemOx significantly improved OS compared with R-GemOx, offering an additional treatment option in patients with transplant-ineligible R/R DLBCL.